Bringing down the Iron Curtain : paradigmatic change in research on the Bronze Age in Central and Eastern Europe? - Sabatová, Klára; Dietrich, Laura; Dietrich, Oliver; Harding, Anthony; Kiss, Viktória (Archaeopress Archaeology, 2020)
Since the fall of communism, archaeological research in Central and Eastern European countries has seen a large influx of new projects and ideas, fueled by bilateral contacts, Europe-wide circulation of scholars and access to research literature. This volume is the first study which relates these issues specifically to Bronze Age Archaeology.